Wakalah bil Ujrah Perspective in the Sharia Compliance Analysis of Hajj Fund Placement within the Indonesia Investment Authority - Lia Indah Khilmina Khilmina; Nanang Apriliyanto; Dul Jalil (Faculty of Islamic Studies, 2026)
This study aims to analyze the legal aspects and sharia compliance related to the placement of Hajj funds by the Hajj Financial Management Agency (BPKH) into the Sovereign Wealth Fund (SWF) or Investment Management Institution (LPI) for infrastructure financing. The main focus of this study is to review the implementation of the Wakalah bil Ujrah contract which forms the basis of the mandate for managing funds from pilgrims to BPKH, as well as compliance with the principle of prudent investment. The research method used is normative juridical with a statutory approach (statute approach) and a conceptual approach (conceptual approach). Secondary data were obtained through legal literature, laws and regulations such as Law No. 34 of 2014 concerning Hajj Financial Management, and Fatwas from the National Sharia Council-Indonesian Ulema Council (DSN-MUI). The research results indicate that legally, the placement of Hajj funds in a SWF is permissible as long as it meets the direct investment criteria stipulated in national regulations. However, from the perspective of the Wakalah bil Ujrah contract, the BPKH, as the representative, must ensure that the selected infrastructure sector has a measurable risk profile to avoid harming the trust of the Muwakkil (congregation). This placement must comply with the principles of Prudent Investment, which encompass aspects of liquidity, solvency, and yield. This research concludes that strict risk mitigation mechanisms and transparent reporting are necessary to ensure that investments in long-term infrastructure projects do not disrupt the availability of funds for the Hajj pilgrimage.